Infrared Sensor Kit as a Speed Detector in the Practicum of Energy and Momentum Laws - Mudhofir, Faiz; Effendy, Suhardi; Linuwih, Suharto; Sulhadi, Sulhadi (Journal of Innovative Science Education, 2019)
Material law of conservation of energy and momentum is abstract material. Practical tools are needed in learning to prove the law so that it can foster real learning for students. This research method is an experimental method that aims to find out how to test the energy conservation and momentum law practicum kit. The practicum kit consists of wheeled objects as loads, precision rails as slippery trajectories, and infrared sensor devices to detect the speed of motion of objects. The kits that have been compiled are then validated by experts before use. Kit validation results are valid. In the implementation of the kit testing the independent variables selected are object mass and slope height. The test results obtained that the kit equipped with infrared sensors is quite accurate in explaining the law of conservation of energy which is evidenced by the relative error that occurs is quite small, namely 1%. In testing the law of conservation of momentum obtained the result that the momentum value of the two objects before the collision approaches the momentum value after the collision. The kit testing results become a solution and innovation as a practical tool to help with more tangible learning.